Physical Properties of Polymer Concrete Utilizing Pahae Natural Zeolite, Corn Husk Fiber, and Polyurethane Resin Adhesives - Maghfirah, Awan; Zega, Adelina Febriyanti (Talenta Publisher, 2024)
This study aimed to determine the optimum composition in the manufacture of polymer concrete using Pahae natural zeolite, corn husk fiber, and polyurethane resin adhesives. This study used the hot-press method at 170â„ƒ for 30 minutes. The compositions of zeolite and corn husk fiber tested were varied under three different additions of polyurethane resin of 15 g, 20 g, and 25 g, while the composition of sand was fixed at 60 g. The inclusion of corn husk fiber content reduces the density of the concrete and increases the porosity and water absorption. The physical properties analysis showed that the polymer concrete samples showed the highest density was 1.89 g/cm3 from 20 g of polyurethane resin and no addition of corn husk fiber; the highest porosity was 6.15% from 15 g of polyurethane resin and 10 g of corn husk fiber; and the highest water absorption was 5.85% from 15 g of polyurethane resin and 10 g of corn husk fiber. Because improved material quality and durability are linked to reduced water absorption rates in polymer concrete, the most favorable composition with minimal water absorption (0.51%) came from the sample utilizing 20 grams of polyurethane resin without incorporating corn husk fiber.